Single cell transcriptome revealed SARS-CoV-2 entry genes enriched in colon tissues and associated with coronavirus infection and cytokine production (2020)
Dear Editor, The novel COVID-19 coronavirus (SARS-CoV-2) endangers thousands of lives. Recently, nearly 10% COVID-19 patients with symptoms of the digestive tract were subsequently diagnosed in newly discovered SARS-CoV-2 infected cases,1 which indicates that SARS-CoV-2 may infect people via digestive systems. The expression profile of angiotensin-converting enzyme homolog 2 (ACE2) has been analyzed in gastrointestinal tract using external datasets. Unfortunately, most data of these datasets are not from Asian adults and the expression of other SARS-CoV-2 entry genes have not been detected in human gastrointestinal tract. Therefore, to provide more implications of viral transmission in clinical diagnosis and treatment, it is urgent to explore the expression of SARS-CoV-2 entry genes in the gastrointestinal tract of Asian people. Here, we used single-cell RNA sequencing profiled ~27,800 cells of intestinal tissues from six patients with basic intestinal disease of Renji hospital.